Pengaruh Pelatihan Metode Prices Terhadap Keterampilan Penanganan Cedera Strain Pada UKM KNC-Emergency - Rahma Shela, Yeni; Rima Agustin, Wahyu Rima Agustin; Setiyawan, Setiyawan (Universitas Haji Sumatera Utara, 2025)
Strain injuries are injuries caused by excessive stretch or tear of the muscles or tendons, calves, groin, hamstring muscles, back and legs. The first 24 hours of treatment can use Protect, Rest, Ice, Compression, Evaluation, and Support for this method (PRICES) will be given as soon as possible. When a player is injured to prevent unresolved injuries the provision of help. The purpose of this study was to determine the skills of handling strain injuries using the PRICES method. The type of research conducted was quantitative pre-experimental with the Quasy Experimental method with the design of one group pretest - postes Without Control Group Design. This study used a sample of 37 respondents. In this study using the Wilcoxon test analysis and the intervention was carried out on March 14, 2024 at Kusuma Husada University Surakata using an observation sheet instrument by collecting data conducted pre test and post test. The results of the study prove that the data obtained have significant changes in the skill variables before and after training for KNC-E members with a p value <0.05. The conclusion that can be drawn with the PRICES method training can improve the skills of KNC-E members, it is hoped that KNC-E members can apply it in health team activities.